Peningkatan Kesadaran Mahasiswa dalam Melakukan Pengawasan Partisipatif pada Pemilu 2024 - Nila Wahyuni; Malse Yulivestra; Ria Ariany; Yona Tri Maulina; Ahmad Syauqi Rizal (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2024)
Elections are one of the pillars of democracy that must maintain integrity and credibility. However, there are still various issues and potential for fraud that can endanger the electoral process. Participatory oversight is needed from various parties because this is the responsibility of The Election Supervisory Agency, The Election Supervisory Committee, and the general public, especially students. As agents of change, students are considered to have great potential in overseeing future electoral processes. This Community Service activity aims to increase students' awareness of conducting participatory oversight in the 2024 General Elections. The partners in this activity are student representatives from various fields of study at Andalas University. The method used in this activity is andragogy, where the facilitator is tasked with facilitating the learning process for students to create an enjoyable learning atmosphere. The activity starts with a pre-test to measure participants' initial abilities before the intervention (socialization), followed by discussions, question-and-answer sessions, and case-solving. The final stage is to administer a post-test to measure participants' abilities after the socialization. The results of the community service activity show an increase in participants' understanding of participatory oversight, marked by an increase in test scores. The average score during the pre-test was 7.82 points, which increased to 9.95 points in the post-test